EzASP – Making Learning Answer Set Programming Easier: Thesis Report - Henriques, Ramiro Miguel Ribeiro (2024)
n recent years, Answer Set Programming (ASP) has gained significant traction as a logic-based method for addressing complex combinatorial problems across various domains such as management, healthcare, and engineering. Despite its effectiveness in finding potential solutions, ASP presents a steep learning curve for beginners due to its unconventional syntax, rooted in declarative programming principles unfamiliar to users accustomed to more traditional programming approaches. To mitigate this challenge, Fandinno et al. argue that the lack of structure in ASP encodings, although highly appreciated by experienced answer set programmers, can lead to confusion for newcomers. They then propose Easy Answer Set Programming, a methodology that emphasizes the importance of structure in ASP and aims to simplify the learning process of Answer Set Programming. However, no existing technology has implemented this methodology in practice. This dissertation fills this void by creating a Visual Studio Code extension, which builds upon two existing extensions aimed at enhancing the ASP user experience. Our extension incorporates the Easy ASP methodology, offering a practical platform for its implementation, even across multiple files. The extension also provides a range of extra features, such as syntax checking, on-hover messages and warnings for missing comments. All the features underwent an evaluation process involving students from relevant courses, eliciting both qualitative and quantitative feedback to assess its efficacy in supporting ASP learners. Ultimately, the results of this evaluation affirmed that the Easy ASP methodology does indeed facilitate students in understanding ASP concepts.